2014
DOI: 10.1073/pnas.1417147111
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog-regulated atypical PKC promotes phosphorylation and activation of Smoothened and Cubitus interruptus in Drosophila

Abstract: Significance Hedgehog (Hh) signaling by Smoothened (Smo) is mediated by phosphorylation and cell surface/cilium accumulation, but how the localization of Smo is controlled remains poorly understood. We show that the atypical PKC (aPKC)–partition defective 6 (Par6) complex promotes Hh signaling by phosphorylating Smo and regulating Smo basolateral accumulation in addition to phosphorylating the transcription factor cubitus interruptus (Ci). Our results demonstrate direct involvement of aPKC in Hh sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 52 publications
1
42
0
Order By: Relevance
“…Additionally, studies of basal cell carcinomas revealed that Prkci can phosphorylate and activate Gli1, thereby potentiating Hh signaling (Atwood et al, 2013). Similarly, in flies, aPKC, a Prkci homolog, can phosphorylate and activate Smo and the Gli homolog Ci, leading to expression of Hh target genes, including aPKC (Jiang et al, 2014b). Thus, the apical Par polarity protein complex might regulate Hh signaling directly, via Gli1 activation, and indirectly, via modulation of cilia dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, studies of basal cell carcinomas revealed that Prkci can phosphorylate and activate Gli1, thereby potentiating Hh signaling (Atwood et al, 2013). Similarly, in flies, aPKC, a Prkci homolog, can phosphorylate and activate Smo and the Gli homolog Ci, leading to expression of Hh target genes, including aPKC (Jiang et al, 2014b). Thus, the apical Par polarity protein complex might regulate Hh signaling directly, via Gli1 activation, and indirectly, via modulation of cilia dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Drosophila S2 cells 54 were transfected with ub-Gal4, UAST-NT, and individual dsRNAs 55 to inhibit the expression of NTR-like receptors CG9918 (nucleotides 11~570), CG8784 (nucleotides −72~478), CG8795 (nucleotides −203~343), Capa (nucleotides 1–455) or GFP control (nucleotides 6–606) using Effectene (Qiagen). Cells (6 x 10 6 ) were dissolved in lysis buffer (450 μL) 48h post-transfection, microcentrifuged (12000 rpm, 10min), and supernatants were analyzed by western blotting.…”
Section: Methodsmentioning
confidence: 99%
“…The extent of phosphorylation of the PKA/ CKI clusters depends on HH levels and controls in a graded manner SMO clustering, the degree of conformational change in its cytotail, its accumulation at the cell surface and its signaling activity Su et al, 2011;Zhao et al, 2007). Moreover, CKIγ/Gilgamesh (Gish), G-protein-coupled receptor kinase 2 (GPRK2/GRK2), Casein kinase II and atypical protein kinase C increase the ability of SMO to transduce high levels of HH by phosphorylating residues present in the membrane-proximal and central regions of the SMO cyto-tail (Jia et al, 2010;Jiang et al, 2014;Li et al, 2016;Maier et al, 2014). In vertebrates, SMO phosphorylation has been reported to depend on GRK2 and CKIγ (Chen et al, 2004).…”
Section: Introductionmentioning
confidence: 99%